Corruption, mafia power and Italian soccer - Testa, Alberto (Routledge research in sport, culture and society, 2018)
chapter 1 Introduction -- chapter 2 Corruption, mafia and the Italian power ‘field’: a Bourdieuian analysis -- chapter 3 Scandals, the ‘sins’ and ‘sinners’ of Italian soccer -- chapter 4 Hidden power: the ‘Calcio’ mafia style -- chapter 5 ‘Ndrangheta and ‘Dirty Soccer’ -- chapter 6 Conclusion – mafia and Italian soccer: the state of the game.